Posterior Fossa Ependymoma in a Child with Extensive Chondro-Osseous Metaplasia Occurring at Cerebellopontine Angle and Masquerading as a Vestibular Schwannoma: An Exceptionally Rare Clinicopathological Manifestation with Review of Literature - Malik, Shaivy; Samanta, Siddhartha Sankar; Kolte, Sachin (Journal of Neurological Surgery Reports, 2024)
Ependymoma occurring at the cerebellopontine (CP) angle is an extremely uncommon sight and poses diagnostic and management dilemmas to neurosurgeons, radiologists, and neuropathologists alike. Moreover, the presence of extensive chondro-osseous metaplastic elements in ependymomas is an exceptionally infrequent histopathological manifestation. However, due to the seldom-seen nature of this histomorphological feature, there is no definite consensus regarding its etiopathogenesis and clinical consequences, and there is an extreme scarcity of literature elucidating its clinicopathological spectrum and prognostic significance. Herein, we illustrate an intriguing clinical tale of a 7-year-old male child with posterior fossa ependymoma, central nervous system (CNS) World Health Organization (WHO) grade 3, arising at the right CP angle and masquerading as a vestibular schwannoma, which in itself is a rare presentation, and additionally, exhibiting extensive chondro-osseous metaplasia, which is a very uncommon histomorphological observation. To the best of the authors' knowledge and after a comprehensive literature search, the coexistence of these two rare observations has merely been described once in international literature. This case sheds light on and highlights the importance of keeping ependymoma as a possible differential while coming across CP angle space-occupying lesions. They should be diligently distinguished from schwannomas and other masqueraders that typically occur at this site, as they have diverse management and follow-up protocols, with varying prognostic outcomes for the patients. Moreover, this case also unravels and details the clinicopathological characteristics of a scarcely described feature of chondro-osseous metaplasia in ependymomas.
Keywords: ependymoma; cerebellopontine angle; chondro-osseous metaplasia; posterior fossa; vestibular schwannoma